Infected femorocele: case report of an extremely rare surgical condition in a middle-aged lady suffering from a painful inguinal swelling - Sabyasachi Bakshi (Surgical Case Reports)
Abstract Background The hydrocele of the femoral hernia sac, an extremely rare occurrence, is termed femorocele. Very few authentically reported cases of femorocele are available in the literature. The present case, diagnosed as a case of infected femorocele, was managed successfully by excision of the femorocele sac and repair of the femoral hernia. To the best of the author’s knowledge, it is the first-ever reported case of infected femorocele. Case presentation A 30-year-old lady presented with a painful 3 cm × 2 cm swelling in the right inguinal region. Though the swelling was there for 2 years, the pain and indurations started after a trivial blunt trauma over the swelling 7 days ago. The patient was febrile and mild tachycardic but had no dysuria. The oval-shaped, tense-cystic, poorly translucent, non-pulsatile, non-reducible swelling showed no cough impulse. There was also a (1.5 cm × 0.5 cm) palpable right-sided superficial inguinal lymph node. Routine blood and urine analysis reports were normal except leukocytosis (10,000/mm3) with neutrophilia. Ultrasonography of the right inguino-labial region revealed a mildly echogenic cystic swelling without any intra-abdominal communication. Exploration of the right inguinal region revealed a cystic (3 cm × 2 cm) swelling, medial to the femoral vessels, containing amber-colored fluid. The distal sac was excised, and anatomical repair of femoral canal defect was done after transfixing the neck of the femorocele sac. Fibro-fatty-collagenous tissue with mixed inflammatory cells along with a flattened mesothelial lining cell layer was found on histopathological examination. Sections from inguinal lymph node showed reactive hyperplasia. Culture of fluid from the sac revealed growth of Escherichia coli. The patient was put on anti-inflammatory drugs and antibiotics according to a sensitivity test. Patient was discharged in stable condition after 5 days. Four months after the operation, the patient is doing well, remaining asymptomatic and without any sign of recurrence. Conclusions The hydrocele of the femoral hernia sac is an extremely rare disease. When not infected, it presents a painless inguinal soft cystic swelling, commonly in women of fourth to sixth decade. This was diagnosed intraoperatively in all cases reported till date. Excision of the sac after transfixation of the neck and anatomical repair are the treatment of choice. In elderly patients, with larger defect, the mesh repair can be opted for. The femorocele may also get infected by uropathogens, and proper antibiotics should be used after a sensitivity test.